Processed ice shelf base picks from airborne radar depth sounding across the Pine Island Glacier Ice Shelf (2010-2011) ... - Corr, Hugh; Vaughan, David (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
In 2011, aerogeophysics data were acquired over Pine Island Glacier, West Antarctica on a grid comprising 30 transverse lines across the glacier, each around 20 km long, and with a spacing of roughly 500 m between the lines. The orientation of the lines was selected to be perpendicular to the surface features visible in satellite images in the central part of the ice shelf. Elevation of the ice‐surface directly beneath the aircraft was simultaneously measured using a nadir‐pointing laser altimeter. We present here the processed bed elevation picks from airborne radar depth sounding collected using the BAS PASIN radar system. Data are provided as XYZ ASCII line data. ... : Radar data and details of survey design and location are presented in Vaughan et al. (2012) and Dutrieux et al. (2013). Radar data were collected using the PASIN radar echo sounding system (table 1 (Corr et al., 2007)). Data provided here includes picks of surface and ice sheet bed elevation. Note a single flight may contain data from two or more SEGY files, identified in the SEGYname channel. Surface elevation is derived from radar altimeter for ground clearance < 750 m, and the PASIN system for higher altitudes. Channel description: Basic Channels Name Description Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_no Line Number e.g. LW200.1 Lon Longitude WGS 1984 Lat Latitude WGS 1984 x x projected meters, coordinate system defined on location page y y projected meters, coordinate system, defined on location page Height_WGS1984 Aircraft altitude (meters) in WGS 1984 Radar segy_name Radar_segy file name (BAS system). TraceNum Radar segy ...